2020
DOI: 10.1002/aorn.13252
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Postoperative Delirium in Older Adult Spine Surgery Patients: A Meta‐Analysis

Abstract: This literature review identifies factors that may place older adult patients at risk for developing delirium after spine surgery. We conducted a meta-analysis according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Using a variety of electronic databases, we identified five studies for inclusion that represent 645 patients who were 65 years or older. The pooled incidence rate of postoperative delirium was 13.0%. Factors associated with developing postoperative deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Preadmission evaluation has many potential benefits, including risk stratification, frailty assessment, identification of the need for postoperative resources in high-risk patients (eg, intensive care and pain services), 31 patient education regarding expectations for pain control and quality of life after the surgery, identification of patients who might benefit from prehabilitation and physiotherapy, and those at risk for postoperative delirium. [33][34][35][36] Commonly reported frailty assessment tools are the frailty index, 37 modified 5-item frailty index, 28 frailty-based score, 38 the clinical frailty scale, 39 the metastatic spinal tumor frailty index, 29,40 and the FRAIL scale. 34 It is hypothesized that the surgical procedure may improve postoperative frailty if deficits improve.…”
Section: Preadmission Assessment and Interventionsmentioning
confidence: 99%
“…Preadmission evaluation has many potential benefits, including risk stratification, frailty assessment, identification of the need for postoperative resources in high-risk patients (eg, intensive care and pain services), 31 patient education regarding expectations for pain control and quality of life after the surgery, identification of patients who might benefit from prehabilitation and physiotherapy, and those at risk for postoperative delirium. [33][34][35][36] Commonly reported frailty assessment tools are the frailty index, 37 modified 5-item frailty index, 28 frailty-based score, 38 the clinical frailty scale, 39 the metastatic spinal tumor frailty index, 29,40 and the FRAIL scale. 34 It is hypothesized that the surgical procedure may improve postoperative frailty if deficits improve.…”
Section: Preadmission Assessment and Interventionsmentioning
confidence: 99%
“…The wide range of the reported incidence in the literature may be partly due to different inclusion criteria such as age, the type of spine surgery, use of instrumentation, the methods used for, and the frequency of, assessing for delirium. The average reported rate of postoperative delirium in the literature appears to be greater in prospective studies compared to retrospective ones (35% vs. 11%) [3,4,[21][22][23][24] A meta-analysis including two prospective studies and three retrospective ones reported an incidence of 13%. [4] Moreover, delirium waxes and wanes 1 and even twice daily assessments as performed at our institution could have missed delirious episodes.…”
Section: Discussionmentioning
confidence: 98%
“…The average reported rate of postoperative delirium in the literature appears to be greater in prospective studies compared to retrospective ones (35% vs. 11%) [3,4,[21][22][23][24] A meta-analysis including two prospective studies and three retrospective ones reported an incidence of 13%. [4] Moreover, delirium waxes and wanes 1 and even twice daily assessments as performed at our institution could have missed delirious episodes. Therefore, given the fluctuating nature of delirium and the retrospective nature of this study, it is possible that the true incidence of postoperative delirium is higher than we observed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations